2021
DOI: 10.1051/0004-6361/202140630
|View full text |Cite
|
Sign up to set email alerts
|

The role of AGN and obscuration in the position of the host galaxy relative to the main sequence

Abstract: We use X-ray active galactic nuclei (AGN) observed by the Chandra X-ray Observatory within the 9.3 deg2 Boötes field of the NDWFS to study whether there is a correlation between X-ray luminosity (LX) and star formation rate (SFR) of the host galaxy, at 0.5 < z < 2.0, with respect to the position of the galaxy to the main sequence (SFRnorm). About half of the sources in the X-ray sample have spectroscopic redshifts. We also construct a reference galaxy catalogue. For both datasets we use photometric data … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
136
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
2

Relationship

5
2

Authors

Journals

citations
Cited by 34 publications
(158 citation statements)
references
References 86 publications
18
136
4
Order By: Relevance
“…Some previous studies found a correlation between N H and M * (Buchner et al 2017;Lanzuisi et al 2017). However, other X-ray studies found that X-ray absorbed and unabsorbed AGN live in galaxies with similar stellar mass (Merloni et al 2014;Masoura et al 2021;Mountrichas et al 2021b). In our sample, most type 1 sources have lower N H values (median of log [N H (cm −2 ) = 20.60) compared to type 2 sources (median of log [N H (cm −2 )] = 21.49), but the distribution of the latter is very broad (Fig.…”
Section: Comparison Of Host Galaxy Properties Of Type 1 and 2 Agnmentioning
confidence: 95%
See 3 more Smart Citations
“…Some previous studies found a correlation between N H and M * (Buchner et al 2017;Lanzuisi et al 2017). However, other X-ray studies found that X-ray absorbed and unabsorbed AGN live in galaxies with similar stellar mass (Merloni et al 2014;Masoura et al 2021;Mountrichas et al 2021b). In our sample, most type 1 sources have lower N H values (median of log [N H (cm −2 ) = 20.60) compared to type 2 sources (median of log [N H (cm −2 )] = 21.49), but the distribution of the latter is very broad (Fig.…”
Section: Comparison Of Host Galaxy Properties Of Type 1 and 2 Agnmentioning
confidence: 95%
“…For the latter, we use expression (9) of Schreiber et al (2015). As mentioned in Mountrichas et al 2021b, using an expression from the literature to calculate the SFR of star-forming MS galaxies and compare it with the SFR of X-ray AGN to estimate SFR norm , hints at a number of systematics. For example, different methods and/or (SED fitting) algorithms may be used in the estimation of SFR and different definitions of MS may be applied in different studies.…”
Section: Properties Of Type 1 and Type 2 X-ray Agnmentioning
confidence: 99%
See 2 more Smart Citations
“…In the SED fitting analysis, we use the same grid used in Mountrichas et al (2021c). This allows us to avoid any systematic effects introduced by using different modules and parameter space during the SED fitting process and facilitates a better comparison with the results presented in the Mountrichas et al study.…”
Section: X-cigalementioning
confidence: 99%